Caracterização física de um solo construído na área de mineração de carvão de Candiota - RS. - Franco, Andrea Machado Pereira (2006)
Coal mining has a key role for the Brazilian economy since the lack of electric energy due to a lower availability of hydric resources is a subject of major concern, therefore it has become necessary a larger scale coal extraction, which promotes a considerable increase in the impacts on the environment. Among these impacts, are the soil and the water degradation, air pollution, acid rain, biodiversity reduction, need of population resettling, which directly affects the quality of life and sustainability of the population of the region. It is thus necessary that the environmental legislation be accomplished by the reclamation of the area where the coal was extracted from, the soil being one the most affected part. In the restoration of the area, it can be pointed out the landscape recovery and the construction of the soil. In this stage the soil physical attributes are negatively affected, attaining undesired physical conditions to the reestablishment of the ecological balance and the return to productive activities. In this context, this study had the objective of characterizing the initial stage of the physical conditions of a constructed soil under a revegetating experiment and compare the results to those obtained in a natural soil located in the mining area front. The following determinations were done: aggregates stability in different size classes, mean weight diameter (MWD), organic carbon, soil bulk density, total porosity, macro/microporosity, particles density, size particle distribution, water disperse clay, mechanical resistance to penetration and available water. The experiment installed in a recent constructed site is comprised of four randomized blocks with seven treatments. In each treatment it was collected three samples in the 0.0 - 0.10 m and 0.10 0.20 m layers. The natural soil samples were collected at 40 points, 3 m apart, along a 117 m transect, in the 0.0 - 0.10 m and 0.10 0.20 m layers. The results obtained showed that: 1) There were no statistical differences in 8 the constructed soil physical attributes in the experiment treatments; 2) Compared to the natural soil, the constructed soil presented lower hierarchic aggregation, organic matter content and available water, and higher clay and mechanical resistance to penetration for both surface and subsurface layers; 3) the constructed soil presented a higher water disperse clay and a lower MWD in the 0.0-0.10 m layer and higher bulk density and mechanical resistance to penetration in the 0.10-0.20 m layer; 4) The constructed soil clay and organic carbon content, and 2.5YR hue color indicates that the soil was constructed with the B horizon of the natural soil; 5) The values of mechanical resistance to penetration obtained in the constructed soil are, in both layers, much higher than the ones considered limiting to plant root development.